Roles of metal ions in the selective inhibition of oncogenic variants of isocitrate dehydrogenase 1 - Liu, S; Abboud, MI; John, T; Mikhailov, V; Hvinden, I; Walsby-Tickle, J; Schofield, CJ; Liu, X; Pettinati, I; Cadoux-Hudson, T; McCullagh, JSO (Springer Nature, 2021)
Cancer linked isocitrate dehydrogenase (IDH) 1 variants, notably R132H IDH1, manifest a ‘gain-of-function’ to reduce 2-oxoglutarate to 2-hydroxyglutarate. High-throughput screens have enabled clinically useful R132H IDH1 inhibitors, mostly allosteric binders at the dimer interface. We report investigations on roles of divalent metal ions in IDH substrate and inhibitor binding that rationalise this observation. Mg2+/Mn2+ ions enhance substrate binding to wt IDH1 and R132H IDH1, but with the former manifesting lower Mg2+/Mn2+ KMs. The isocitrate-Mg2+ complex is the preferred wt IDH1 substrate; with R132H IDH1, separate and weaker binding of 2-oxoglutarate and Mg2+ is preferred. Binding of R132H IDH1 inhibitors at the dimer interface weakens binding of active site Mg2+ complexes; their potency is affected by the Mg2+ concentration. Inhibitor selectivity for R132H IDH1 over wt IDH1 substantially arises from different stabilities of wt and R132H IDH1 substrate-Mg2+ complexes. The results reveal the importance of substrate-metal ion complexes in wt and R132H IDH1 catalysis and the basis for selective R132H IDH1 inhibition. Further studies on roles of metal ion complexes in TCA cycle and related metabolism, including from an evolutionary perspective, are of interest.